The ventilatory response to hypoxia is blunted in some preterm infants during the second year of life - Freislich, Zoe; Stoecklin, Benjamin; Hemy, Naomi; Pillow, J. Jane; Hall, Graham L.; Wilson, Andrew C.; Simpson, Shannon J. (Frontiers in Pediatrics, 2022)
Background: Preterm birth and subsequent neonatal ventilatory treatment disrupts development of the hypoxic ventilatory response (HVR). An attenuated HVR has been identified in preterm neonates, however it is unknown whether the attenuation persists into the second year of life. We investigated the HVR at 12-15 months corrected postnatal age and assessed predictors of a blunted HVR in those born very preterm (< 32 weeks gestation). Methods: HVR was measured in infants born very preterm. Hypoxia was induced with a three-step reduction in their fraction of inspired oxygen (FIO2) from 0.21 to 0.14. Respiratory frequency (f), tidal volume (VT), minute ventilation (VE), inspiratory time (tI), expiratory time (tE), VT/tI, tI/tTOT, VT/tTOT, area under the low-volume loop and peak tidal expiratory flow (PTEF) were measured at the first and third minute of each FIO2. The change in respiratory variables over time was assessed using a repeated measures ANOVA with Greenhouse-Geisser correction. A blunted HVR was defined as a <10% rise in VE, from normoxia. The relationship between neonatal factors and the magnitude of HVR was assessed using Spearman correlation. Results: Thirty nine infants born very preterm demonstrated a mean (SD) HVR of 11.4 (10.1)% (increase in VE) in response to decreasing FIO2 from 0.21 to 0.14. However, 17 infants (44 %) failed to increase VE by ≥10 % (range -14 % to 9 %) and were considered to have a blunted response to hypoxia. Males had a smaller HVR than females (ΔVE (-9.1 %; -15.4, -2.8; p=0.007)). Conclusion: Infants surviving very preterm birth have an attenuated ventilatory response to hypoxia that persists into the second year of life, especially in males.